Analisis Ergonomi Fasilitas Pintu Kelas Fakultas Teknik Universitas X - Nabila Shafira Dewi; Pramestari, Diah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
The effectiveness of the educational process, comfort, and safety are all greatly enhanced by an ergonomic learning environment. The layout of classroom facilities, which includes doors as the main access and departure points, is one area that needs consideration. This study uses student anthropometrics and ergonomic principles to examine the ergonomics of classroom doors on the eighth floor of University X’s Faculty of Engineering. Students enrolled in an industrial ergonomics course were directly measured as part of the quantitative research methodology. Height, shoulder breadth, standing elbow height, handgrip diameter, and maximum thumb-to-pinky finger width were among the anthropometric measurements that were gathered. The optimal door dimensionsâ€”height, width, handle height, handle diameter, and handle lengthâ€” were then determined by analyzing the student’s anthropometric dataThe findings demonstrated that the only door handle diameter that was both ergonomic and in line with the anthropometric measurements of the students was 5 cm. At 216 cm, the door height goes above the ideal size of 199.4 cm; at 80 cm, the door width falls short of the ideal size of 103.3 cm; at 116 cm, the handle height goes above the ideal size of 106.8 cm; and at 11 cm, the handle length falls short of the ideal size of 15.5 cm. Discomfort and an increased risk of musculoskeletal problems could result from these dimensional differences. As a consequence, the study suggests changing the design of classroom doors to make them more user-friendly, secure, and ergonomic.